Gender Preferences and Job Performance in University Teachers: A Case Study of Azad Jammu & Kashmir - Sidra Jamil; Nazish Jamil; Saira Maroof; Sadia Sadeeq; Dr. Muhammad Shabbir* (Dialogue Social Science Review (DSSR), 2025)
The research was conducted under the title “Gender Preferences and Job Performance among University Teachers: Evidence from Azad Jammu and Kashmir.” The primary aim of this study was to examine how factors such as gender, age, academic qualifications, and job security influence the performance of university teachers in AJK. For this purpose, data were collected using a structured questionnaire administered to 227 university teachers who were randomly chosen from three universities located in the districts of Bagh, Muzaffarabad, and Poonch. The data were analyzed with the help of the Statistical Package for Social Sciences (SPSS 20), employing descriptive statistics, ANOVA, and regression analysis. The findings indicated that male teachers, on average, showed higher job performance compared to their female counterparts. Younger faculty members were observed to perform better than older ones, largely because of their updated knowledge and ability to apply it in line with contemporary requirements. Similarly, teachers holding higher academic qualifications exhibited stronger job performance than those with lower qualifications. Furthermore, unmarried teachers were found to be more focused on their professional responsibilities, whereas married teachers faced additional family-related obligations that appeared to affect their performance at work.